2023
DOI: 10.1002/admt.202202179
|View full text |Cite
|
Sign up to set email alerts
|

Aligned Phthalocyanine Molecular Nanowires by Graphoepitaxial Self‐Assembly and Their In Situ Integration into Photodetector Arrays

Abstract: Large-scale on-chip integration of organic nanowire-based devices requires the deterministic assembly of organic small molecules into highly-aligned nanowires. In this work, phthalocyanine molecules are self-assembled into horizontally-aligned nanowires after generating parallel hydrophobic nanogrooves on a sapphire surface. In contrast to previous self-oriented inorganic nanowires, these molecular nanowires are separated from their supporting sapphire by an ultrathin amorphous layer, indicating a complete eli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 77 publications
0
12
0
Order By: Relevance
“…High magnification SEM observation (Figure 1c; Figure S1, Supporting Information) reveals that these nanowires grow in parallel along the direction defined by the nanogrooves, instead of the symmetric crystallographic orientations of the underlying sapphire. [ 46,48–50 ] The X‐ray diffraction (XRD, Figure S2, Supporting Information) and Raman spectra (Figure S3, Supporting Information) of these nanowires match that of the CuPc powder, hence, no chemical reaction occurs during the vapor deposition process. Figure 1d shows a representative device with 16 × 16 arrays of gold electrodes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…High magnification SEM observation (Figure 1c; Figure S1, Supporting Information) reveals that these nanowires grow in parallel along the direction defined by the nanogrooves, instead of the symmetric crystallographic orientations of the underlying sapphire. [ 46,48–50 ] The X‐ray diffraction (XRD, Figure S2, Supporting Information) and Raman spectra (Figure S3, Supporting Information) of these nanowires match that of the CuPc powder, hence, no chemical reaction occurs during the vapor deposition process. Figure 1d shows a representative device with 16 × 16 arrays of gold electrodes.…”
Section: Resultsmentioning
confidence: 99%
“…We first prepared high‐density oriented CuPc nanowires with lengths of 50–150 µm on an annealed M‐plane sapphire surface ( Figure a) by evaporating commercially available CuPc powder at 240 °C. [ 46–48 ] These nanowires are then stored at ambient conditions without special protection (e.g., vacuum or inert gas). Even with high‐velocity gas flow, it is impossible to remove these self‐oriented nanowires from their growth substrate, indicating that these self‐oriented nanowires have a much stronger interaction with their underlying substrate than the commonly reported freestanding nanowires.…”
Section: Resultsmentioning
confidence: 99%
“…However, as the gaseous precursor feeding in VLS growth tends to produce vertical bundles of standing SiNWs, they need to be collected, transferred and rearranged into precise locations on planar surface for reliable logic device integration . Though many research efforts have been developed to achieve planar growth of VLS SiNWs, , surface faceted groove-guided planar growth, , or postgrowth rearrangement of them, , a scalable integration of orderly VLS-grown SiNWs on planar surface is still missing.…”
Section: Introductionmentioning
confidence: 99%
“…Up to now, various methods have been proposed for the assembly of 1D nanostructures, such as roll printing strategy, contact printing, dielectrophoretic assembly, nanoscale combing technique, magnetic field alignment, etc . Although these methods have proven successful in large-scale directional arrangement of 1D nanostructures, they have their own drawbacks, such as the tendency to damage nanowires, the limited length of nanowires, etc. To overcome the drawbacks of postgrowth assembly of 1D nanostructures, a graphoepitaxy technology has been proposed. This method usually refers to the use of periodic nanofeatures (e.g., nanogrooves or nanosteps) on a substrate surface to achieve directional assembly of atoms or molecules . For example, as early as 1996, Sunamura et al observed the self-organized growth of Ge quantum wires at step edges on Si(100) by its lateral confinement effect .…”
Section: Introductionmentioning
confidence: 99%
“…They later achieved the guided growth of millimeter-long GaN nanowires along the nanogrooves of the annealed M-plane (101̅0) sapphire . Up to now, the generality of graphoepitaxial growth has been widely demonstrated in the horizontally oriented growth of various 1D inorganic (e.g., ZnTe, ZnSe, ZnO, CdSe, and CdS) or organic (e.g., metal phthalocyanines, Alq3) nanowires on various substrates (such as SiC, quartz, and spinel). ,,, …”
Section: Introductionmentioning
confidence: 99%